The factors affecting burnout among community pharmacists in Vietnam: a community-based cross-sectional study - Le, Tran Tuan Anh; Ngo, Thi Kim Cuc; Vo, Thi Tan Tien; Nguyen, Phuoc Bich Ngoc; Nguyen, Thi Phuong Thao; Tran, Nhu Minh Hang; Le, Chuyen (Tạp chí Y Dược Huế, 2024)
Objectives: This study investigated burnout prevalence and its risk factors among community pharmacists in Vietnam. Methods: An interview-based cross-sectional study on 362 pharmacists working in pharmacies in Hue City between January and June 2023 was conducted. Data were collected using a Vietnamese interview questionnaire that included socio-demographic characteristics, work-related variables, and knowledge, attitudes, and practices regarding the role of community pharmacists in Hue in improving community health. Burnout status was assessed using the validated Vietnamese version of the Copenhagen Burnout Inventory (CBI-V). Results: The prevalence of personal, work-related, and client-related burnout was 12.7, 12.4 and 11.6%. 53.3% occasionally felt work-related tiredness, with a third feeling exhausted at the end of the workday. Difficulties in working with clients (39.2%) and a sense of giving more than receiving from clients (34.8%) were significant. A higher work-related burnout rate was reported with negative attitudes. Meanwhile, factors such as workplace, customer volume, and pharmacists’ knowledge and attitudes were linked to client-related burnout. Conclusion: This study emphasizes the importance of developing strategies to mitigate burnout and maintain pharmaceutical care quality and pharmacist well-being